Political and civic participation of women - Bergano, Sofia (2019)
With this chapter we intend to reflect on how women interpret their political and civic participation in Portuguese society. In Portugal formal changes in this area have happened at a fast pace and have witnessed a growing political, academic and social interest in female participation in the public sphere. Being aware of these phenomena, it is important to try to understand how these changes are interpreted by women of different ages and from different social backgrounds. As indicated in the literature review, the participation of women in the public sphere is the result of a range of social factors including schooling and family education, the perpetuation of stereotypes that associate the exercise of power to the male gender, the legal recognition of citizenship rights, as well as many other social factors.